GOLM1-induced Vascular Permeability and Angiogenesis in Hepatocellular Carcinoma through Modulation of Cancer Cell-derived ExosomalmicroRNAs - Yu, Kangkang; Huo, Meisi; Cai, Fujing; Zheng, Yahui; Yin, Ruiqi; Ding, Jiguang; Huang, Chong; Zhang, Jubo (Current Cancer Drug Targets, 2025)
<span class=
Keywords: exosome